5‐Hydroxytryptophan, a precursor for serotonin synthesis, reduces seizure‐induced respiratory arrest. (15th June 2016) - Zhang, Honghai; Zhao, Haiting; Yang, Xiaoxuan; Xue, Qingsheng; Cotten, Joseph F.; Feng, Hua‐Jun
Summary: Objective: The DBA/1 mouse is a relevant animal model of sudden unexpected death in epilepsy (SUDEP), as it exhibits seizure‐induced respiratory arrest (S‐IRA) evoked by acoustic stimulation, followed by cardiac arrhythmia and death. Defects in serotonergic neurotransmission may contribute to S‐IRA. The tryptophan hydroxylase‐2 (TPH2) enzyme converts L‐tryptophan to 5‐hydroxytryptophan (5‐HTP), a precursor for central nervous system (CNS) serotonin (5‐HT) synthesis; and DBA/1 mice have a polymorphism that decreases TPH2 activity. We, therefore, hypothesized that supplementation with 5‐HTP may bypass TPH2 and suppress S‐IRA in DBA/1 mice. Methods: TPH2 expression was examined by Western blot in the brainstem of DBA/1 and C57BL/6J mice both with and without acoustic stimulation. Changes in breathing and cardiac electrical activity in DBA/1 and C57BL/6J mice that incurred sudden death during generalized seizures evoked by pentylenetetrazole (PTZ) were studied by plethysmography and electrocardiography. The effect of 5‐HTP administration on seizure‐induced mortality evoked by acoustic stimulation or by PTZ was investigated in DBA/1 mice. Results: Repetitive acoustic stimulation resulted in reduced TPH2 protein in the brainstem of DBA/1 mice as compared with C57BL/6J mice. S‐IRA evoked by acoustic stimulation in DBA/1 mice was significantly reduced by 5‐HTP. Following S‐IRA, cardiac electrical activity could be detected for minutes before terminal asystole and death in both DBA/1 and C57BL/6J mice after PTZ treatment. The incidence of S‐IRA by PTZ administration was greater in DBA/1 than in C57BL/6J mice, and administration of 5‐HTP also significantly reduced S‐IRA by PTZ in DBA/1 mice. Significance: Our data suggest that S‐IRA is the primary event leading to death incurred in most DBA/1 and some C57BL/6J mice during PTZ‐evoked seizures. Suppression of S‐IRA by 5‐HTP suggests that 5‐HT transmission contributes to the pathophysiology of S‐IRA, and that 5‐HTP, an over‐the‐counter supplement available for human consumption, may be clinically useful in preventing SUDEP.